N-[4-(Phenyliminomethyl)phenyl]acetamide 0.67-hydrate - Mahmud, Tariq (International Union of Crystallography, 2010)
The title compound, C(15)H(14)N(2)O·0.67H(2)O, was prepared by the reaction of 4-acetoaminebenzaldehyde and aniline. The asymmetric unit contains six organic molecules and four water molecules. The dihedral angles between the aromatic ring planes in each organic molecule vary from 42.4 (2) to 53.8 (2)°. In the crystal, an extensive network of intermolecular N—H⋯O, O—H⋯N and O—H⋯O hydrogen bonds link the molecules into [010] chains.